2005
DOI: 10.1111/j.0959-9673.2005.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of water‐soluble amyloid‐β in the pathogenesis of Alzheimer's disease

Abstract: SummaryWater-soluble amyloid-b (wsAb) is present in cerebral cortex of subjects at risk of Alzheimer's disease (AD) as well as in normal elderly subjects as a mixture of three major amyloid-b (Ab) species: 1-42, py3-42 and py11-42. The three wsAb species are nondetectable in brains of young people, free of immunohistochemically detectable amyloid plaques. In the brains of Down's syndrome and APP-mutant transgenic mice, wsAb appears long time before amyloid deposition, indicating that it represent the first for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 52 publications
(77 reference statements)
2
23
0
Order By: Relevance
“…Russo et al (77) showed that cases with a PS1 mutation developed a higher ratio of water-soluble A␤ pE3-42 and A␤ pE11-42 to full-length A␤ in comparison with sporadic AD cases. In line with this observation, water-soluble A␤ from brains of normal elderly individuals with abundant amyloid and neurofibrillary pathology demonstrated a decreased A␤ pE3-42 /A␤ 1-42 ratio compared with AD cases (76). Overall, the ratio of watersoluble A␤ pE3-42 to A␤ seems to be proportional to the clinical phenotype and the severity of the disease.…”
Section: Soluble Oligomeric Pyroglutamate A␤: the Missing Link In A␤ supporting
confidence: 65%
See 1 more Smart Citation
“…Russo et al (77) showed that cases with a PS1 mutation developed a higher ratio of water-soluble A␤ pE3-42 and A␤ pE11-42 to full-length A␤ in comparison with sporadic AD cases. In line with this observation, water-soluble A␤ from brains of normal elderly individuals with abundant amyloid and neurofibrillary pathology demonstrated a decreased A␤ pE3-42 /A␤ 1-42 ratio compared with AD cases (76). Overall, the ratio of watersoluble A␤ pE3-42 to A␤ seems to be proportional to the clinical phenotype and the severity of the disease.…”
Section: Soluble Oligomeric Pyroglutamate A␤: the Missing Link In A␤ supporting
confidence: 65%
“…In DS, water-soluble A␤ appeared early (ϳ20 years before the appearance of the plaques) and increased with age and the progression of the amyloid pathology. Interestingly, water-soluble A␤ increased by 100-fold in young cases accompanied by an increase in A␤ pE3-42 (76). Russo et al (77) showed that cases with a PS1 mutation developed a higher ratio of water-soluble A␤ pE3-42 and A␤ pE11-42 to full-length A␤ in comparison with sporadic AD cases.…”
Section: Soluble Oligomeric Pyroglutamate A␤: the Missing Link In A␤ mentioning
confidence: 99%
“…Others have found in cultured cells intracellular A␤ accumulation derived from the Golgi network and endoplasmic reticulum (18,(22)(23)(24)(25)(26). Piccini et al (27), using immunoprecipitation, have identified A␤ species in soluble extracts of frozen AD and control brain (27,28), but did not examine for tau complexes. Lue et al (29) detected, by ELISA, A␤40 and A␤42 in soluble extracts of frozen entorhinal and superior frontal cortex from AD cases, high pathology controls, and normal controls with AD cases showing the highest level of both A␤ species.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fluvastatin significantly increased A␤ clearance rate at an injected concentration of 10 M (Fig. 6C), whereas it failed to affect A␤ clearance rate at 20 nM and 1 M. As the injected drug was diluted at least 30-fold by diffusion immediately after administration and spread farther (42) and the soluble A␤ level in the brain of AD patients is near or over 100 nM (43)(44)(45), our present study might be relevant in the pathological state of AD rather than in the normal physiological state (physiolog- ical A␤ level is about 1 nM). Because we previously showed that fluvastatin did not affect the activity and level of major A␤-degrading enzymes such as neprilysin and insulin-degrading enzyme in the brain (25), we focused on the levels of apolipoprotein E, P-glycoprotein and the low density lipoproteinrelated protein 1 (LRP1), which are reported to be involved in A␤ clearance from the brain (46).…”
Section: Figure 2 Effects Of Lysosomal Inhibitors On Reduction Of Apmentioning
confidence: 91%